2009
DOI: 10.1243/13506501jet504
|View full text |Cite
|
Sign up to set email alerts
|

The determination of the pressure—viscosity coefficient of a lubricant through an accurate film thickness formula and accurate film thickness measurements

Abstract: The pressure-viscosity coefficient is an indispensable property in the elastohydrodynamic (EHD) lubrication of hard contacts, but often not known. A guess will easily lead to enormous errors in the film thickness. This article describes a method to deduct this coefficient by adapting the value of the pressure-viscosity coefficient until the differences between accurate film thickness approximation values and accurate film thickness measurements over a wide range of values are at a minimum. Eleven film thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…Concerning central film thickness, van Leeuwen [1,2] concluded that for both moderately-loaded and highly-loaded EHD contacts, Chittenden et al [8] formula was the more accurate and that its validity transcended the area where it was originally designed for. As for minimum film thickness, the use of Chevalier ratios [6] combined with the Nijenbanning et al [5] formula has shown, from experimental confrontation, to be the more consistent over very wide ranges of the (M, L) parameters [3].…”
Section: Results and Discussion On Circular Contactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning central film thickness, van Leeuwen [1,2] concluded that for both moderately-loaded and highly-loaded EHD contacts, Chittenden et al [8] formula was the more accurate and that its validity transcended the area where it was originally designed for. As for minimum film thickness, the use of Chevalier ratios [6] combined with the Nijenbanning et al [5] formula has shown, from experimental confrontation, to be the more consistent over very wide ranges of the (M, L) parameters [3].…”
Section: Results and Discussion On Circular Contactsmentioning
confidence: 99%
“…The widely-used expressions mentioned below were selected on the basis of (i) van Leeuwen studies [1,2] and (ii) a previous experimental work [3] in which the capabilities of some of them were quantitatively compared with measurements performed over wide ranges of operating conditions and for numerous lubricants of different nature:…”
Section: Models and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…So long as inlet shear thinning does not occur, the composite piezoviscous response over the inlet region can be measured using high pressure rheometry [3] or estimated directly from measurements of EHD film thickness [4] [5] and applied in regression-based film thickness equations [6]. For polymer solutions and some very high molecular weight base fluids, where inlet shear thinning does occur, its effect can also be taken into account [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…If we assume that at ambient pressure (p = 0), the slopes of the Barus and Roelands equation are equal, then the Barus parameter can be obtained from the Roelands one using [27]:…”
Section: Calculating the Barus And Roelands Pressure Viscosity Coeffimentioning
confidence: 99%